2020
DOI: 10.1038/s41598-020-76415-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of RPTPβ/ζ in neuroinflammation and microglia-neuron communication

Abstract: Pleiotrophin (PTN) is a cytokine that is upregulated in different neuroinflammatory disorders. Using mice with transgenic PTN overexpression in the brain (Ptn-Tg), we have found a positive correlation between iNos and Tnfα mRNA and Ptn mRNA levels in the prefrontal cortex (PFC) of LPS-treated mice. PTN is an inhibitor of Receptor Protein Tyrosine Phosphatase (RPTP) β/ζ, which is mainly expressed in the central nervous system. We aimed to test if RPTPβ/ζ is involved in the modulation of neuroinflammatory respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…MDK deficiency reduces M1 phenotype microglia/macrophage infiltration after TBI 55 . Overexpression of PTN in mice significantly enhances LPS‐induced inflammatory cytokine expression 56,57 . Transplantation of PSAP‐deficient bone marrow into low‐density lipoprotein receptor knockout mice decreases plaque inflammation in atherosclerosis 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MDK deficiency reduces M1 phenotype microglia/macrophage infiltration after TBI 55 . Overexpression of PTN in mice significantly enhances LPS‐induced inflammatory cytokine expression 56,57 . Transplantation of PSAP‐deficient bone marrow into low‐density lipoprotein receptor knockout mice decreases plaque inflammation in atherosclerosis 37 .…”
Section: Discussionmentioning
confidence: 99%
“… 55 Overexpression of PTN in mice significantly enhances LPS‐induced inflammatory cytokine expression. 56 , 57 Transplantation of PSAP‐deficient bone marrow into low‐density lipoprotein receptor knockout mice decreases plaque inflammation in atherosclerosis. 37 These studies suggest that MDK, PTN, and PSAP play a pro‐inflammatory role.…”
Section: Discussionmentioning
confidence: 99%
“…The RPTPβ/ζ signalling pathway is involved in the regulation of the neuroimmune response to different stimuli ( Herradon et al, 2019 ). Accordingly, we have shown that inhibition of RPTPβ/ζ with MY10 potentiates LPS-induced microglial responses ( Fernández-Calle et al, 2020 ). Thus, in the present study we aimed to test the possibility that RPTPβ/ζ inhibition modulates IAE-induced changes in glial responses in the dentate gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…However, also in view of the recent compelling data that come from multiple behavioral studies in mice ( Cressant et al, 2017 ; Fernandez-Calle et al, 2018 ; Fujikawa et al, 2019 ; Tanga et al, 2019 ) it is a matter of time to be able to pinpoint PTPRZ1 variants as components in the multifactorial central nervous system disorders. Studies involving Ptprz1 mutant mice and various cell models have established a regulatory role in neuroinflammation and (re)myelination ( Fujikawa and Noda, 2016 ; Fernandez-Calle et al, 2020 ; Nagai et al, 2022 ), and thus multiple sclerosis as disease link also comes to mind. This is, however, as yet not supported by human PTPRZ1 mutations associating with this chronic inflammatory demyelinating disorder.…”
Section: Documented Genetic Variabilitymentioning
confidence: 99%